Counseling On Oxytocin Massage in Promoting Breast Milk For Breastfeeding Mothers in Bintuju Sub-District - Dewi Aminasty Siregar (IJCS: International Journal of Community Service, 2022)
Insufficient breast milk is the main reason for a mother to stop breastfeeding early, mother feel that he does not have sufficient milk production to meet the needs of the baby and support increase heavy body baby which adequate because breast milk no out or production not enough fluent. Care that effective for multiply production breast milk Among other with To do care breast or breast care with guard cleanliness and (massage) breasts, and massage oxytocin. Massage oxytocin have some very helpful benefits for mothers after childbirth and also can reduce physical discomfort and improve mood. Massages done in along bone behind this could relax tension on back and relieve stress so that it can facilitate the release of breast milk. Meanwhile, according to Department of health RI massage oxytocin could reduce swollen, reduce blockage breast milk, and maintain milk production when mother and baby are sick. Type of research used is quantitative, is research which done with the aim of making description or description something state objectively. Results data collection individual and family where amount mother breast-feed as much 30 person, held with counseling and use tool in the form of questionnaire for measure how mother's knowledge, and it was obtained that knowledge mom about the benefits of oxytocin massage in increase production breast milk majority knowledgeable not enough that is 29 person (96.7%), the minority with sufficient knowledge is 1 person (3.3%) and has good knowledge no there is (0%).